Problems of improving the Kazakhstani model of church-state relations (Journal of actual problems of jurisprudence, 2019)
Kazakhstan’s model of a secular state requires a special approach to the regulation of relations in the sphere of religion. In our stateare living representatives of various faiths, including Muslims, Orthodox, Catholics, Protestants, Buddhists and Jews. The logic of thisidentity is that the inter-ethnic and inter-religious relations are inseparable to each other. Dissemination in the elements of religiousextremist ideology requires special attention and action primarily privintivnogo character.